Development of an Inquiry Learning Model in Islamic Religious Education to Improve Students Critical Thinking Skills at Yayasan Pendidikan Islam Yahdi - Nabillah, Winna; Pasaribu, Munawir; Fanreza, Robie (Lembaga Riset Mutiara Akbar, 2025)
This study aims to develop an inquiry-based learning model in Islamic Religious Education (PAI) to enhance students’ critical thinking skills at Yayasan Pendidikan Islam Yahdi. The core problem identified is that PAI learning remains predominantly teacher-centered, resulting in passive student participation and limited development of critical thinking abilities. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included one Islamic Religious Education teacher and 25 fifth-grade students at SD Swasta Yahdi. Expert validation results showed an average feasibility score of 88.3%, categorized as “Highly Feasible.” The practicality test obtained an average score of 4.45, indicating that the model was “Highly Practical.” During implementation, students demonstrated increased activity, motivation, and reflective thinking in understanding Islamic values. Teachers also reported that the learning process became more interactive, engaging, and meaningful. Overall, the developed inquiry-based learning module was declared feasible, practical, and effective in improving students’ critical thinking skills in Islamic Religious Education at the elementary school level.